1996
DOI: 10.4315/0362-028x-59.12.1292
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Serological and Biological Activities of Staphylococcal Enterotoxin A in Canned Mushrooms

Abstract: Outbreaks in 1989 of staphylococcal food poisoning linked to the consumption of imported canned mushrooms indicated that staphylococcal enterotoxins (SE) may survive a commercial retort process. To examine this possibility, fresh mushrooms were blanched in boiling water for 5 min and cooled 5 min in sterile water inoculated with enterotoxigenic type A Staphylococcus aureus strain 743, to yield approximately 1.3 ×103 staphylococci per g. Inoculated mushrooms were incubated 20 h at 30°C to simulate time-temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…An example of this problem is the lack of differentiation between active and heat inactivated B. cereus enterotoxin by the BCET-RPLA Schultz 1992, 1994). The opposite can also occur: the serological activity of staphylococcal enterotoxin is more heat labile than the biological activity, so false negative results can occur in thermally processed food (Anderson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…An example of this problem is the lack of differentiation between active and heat inactivated B. cereus enterotoxin by the BCET-RPLA Schultz 1992, 1994). The opposite can also occur: the serological activity of staphylococcal enterotoxin is more heat labile than the biological activity, so false negative results can occur in thermally processed food (Anderson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that pasteurizing raw milk would eliminate S. aureus from raw milk; however, once the pathogens have produced the SEs, the toxins will remain stable even after pasteurization [12]. Researchers have shown that SEs are highly resistant to heat treatment; a good example is sea, which retained its biological activity even after exposure to as high temperature as 121°C for 28 minutes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Enterotoxigenic Staphylococcus aureus is a major bacterial pathogen that develops multidrug resistance to antibiotics (Pereira and others 2009; Rhee and Woo 2010; Pu and others 2011). The enterotoxigenic bacteria and secreted toxins have been reported to cause clinical infections and contamination of a broad variety of foods, including breaded chicken products (Pepe and others 2006), canned mushrooms (Anderson and others 1996), cheeses (Ertas and others 2010; Ostyn and others 2010; Rosengren and others 2010), raw milk (Heidinger and others 2009; Fusco and others 2011), pork meat (Wallin‐Carlquist and others 2010), and other foods (Balaban and Rasooly 2000) as well on handles of shopping carts (Mizumachi and others 2011) causing foodborne illnesses in the United States each year (Shinefield and Ruff 2009). Staphylococcal food poisoning is due to the absorption from the digestive tract into the circulation of the enterotoxins preformed in food.…”
Section: Introductionmentioning
confidence: 99%